A cluster randomised controlled trial of a sugar-sweetened beverage intervention in secondary schools: Pilot study protocol. Issue 4 (December 2018) - Ooi, Jia Ying; Sutherland, Rachel; Nathan, Nicole; Yoong, Sze Lin; Janssen, Lisa; Wrigley, Jessica; Wolfenden, Luke
Background: Due to the rising prevalence of overweight and obesity in children and adolescents, reducing childhood overweight and obesity rates is a public-health priority. A significant source of excess sugar and energy in children's diets comes from sugar-sweetened beverages (SSB), with adolescents having the highest intake of all age groups. However, existing interventions targeting SSB intake in adolescents have multiple limitations. Schools have proven to be an appropriate setting for improving student health. Aim: To assess the effectiveness of a school-based SSB intervention in reducing daily SSB consumption and daily percentage energy from SSBs of secondary-school students. Methods: A pilot study ( switchURsip ) was designed based on the Health Promoting Schools framework components. A convenience sample of schools in New South Wales, Australia will be used to recruit six schools (three intervention; three control). The study incorporates strategies that focus on factors associated with SSB intake in adolescents. These strategies include: lesson plans on SSB; communication with students and parents; school challenge to build peer support; and school nutrition environment modifications. Support strategies to facilitate implementation are executive leadership and school committees, auditing and feedback, providing resources, staff professional learning and communication and marketing. Conclusion: The high intake of SSB in adolescents has been consistently linked to having overweight and obesity, hence, interventions in this area should be prioritised. This pilot study intends to address identified evidence gaps by piloting the first intervention in Australia of its kind to reduce SSB intake in adolescents.